Emergency Department Length of Stay for Maori and European Patients in New Zealand - Prisk, David (West J Emerg Med, 2016)
INTRODUCTION: Emergency department length of stay (ED LOS) is currently used in Australasia as a quality measure. In our ED, Maori, the indigenous people of New Zealand, have a shorter ED LOS than European patients. This is despite Maori having poorer health outcomes overall. This study sought to determine drivers of LOS in our provincial New Zealand ED, particularly looking at ethnicity as a determining factor. METHODS: This was a retrospective cohort study that reviewed 80,714 electronic medical records of ED patients from December 1, 2012, to December 1, 2014. Univariate and multivariate analyses were carried out on raw data, and we used a complex regression analysis to develop a predictive model of ED LOS. Potential covariates were patient factors, temporal factors, clinical factors, and workload variables (volume and acuity of patients three hours prior to and two hours after presentation by a baseline patient). The analysis was performed using R studio 0.99.467. RESULTS: Ethnicity dropped out in the stepwise regression procedure; after adjusting for other factors, a specific ethnicity effect was not informative. Maori were, on average, younger, less likely to receive bloodwork and radiographs, less likely to go to our observation area, less likely to have a general practitioner, and more likely to be discharged and to self-discharge; all of these factors decreased their length of stay. CONCLUSION: Length of stay in our ED does not seem to be related to ethnicity alone. Patient factors had only a small impact on ED LOS, while clinical factors, temporal factors, and workload variables had much greater influence.